THE IMPACT OF CUSTOMER INTENTION TO CONTINUE USING INSURANCE SERVICE IN JABODETABEK (CASE OF JIWASRAYA) - Fitriyani Indah Permatasari; Jean Richard Jokhu (President University, 2023)
The writing of this paper aims to explain the influence of the Jiwasraya case on insurance continue using in JABODETABEK. Background of this study because insurance in Indonesia has not experienced a high enough absorption so that the problem of insurance in Indonesia is one indicator in determining whether customer continue using insurance or not. The results showed that satisfaction, trust, loyalty, word of mouth and affective commitment on customer intention to continue using insurance have a simultaneously significant effect. While partially, the trust variable does not have a significant effect on continuing using insurance, this means that the independent variable in the variable model trust, loyalty, satisfaction, affective commitment, word of mouth explains the variation of continue using insurance explained by other factors or variables outside the model.